Multi-sensory congruence for perceived thermal comfort in wellness spaces - Botor, Melanie S.
The present study aimed to identify the typical sensory associations to ambient scents and interior colors whose congruence can affect the perception of thermal comfort in wellness spaces. Utilizing a descriptive applied design, this research identified the typical temperature associations to scents and colors and analyzed the factors that can affect the perception of these stimuli. A purposive sampling strategy was employed to select the research respondents who were asked to accomplish an online questionnaire along with a ‘smell and see kit’ which was used to gather data on respondents’ perceptions on pre-selected scent and color samples along four dimensions aligned with the research objectives: familiarity, suitability to a wellness space, likeability and perceived temperature. A correlation analysis was conducted between respondents’ ratings on the stimuli samples and their sociodemographic information. Results from the online questionnaire indicated that sight is a more dominant sense than smell. In addition, while previous studies have attributed more smell acuity to females, the finding of most females rating ‘vanilla’ as ‘cold’ counter to its expected ‘warm’ association tells us that the ‘cold’ association could come from previous experience due to culture as vanilla is often used as an ice cream flavor. The correlation analysis showed that in the dimensions of familiarity, suitability to a wellness space and likeability, gender and age have a significant effect in interior color preference while marital status affects ambient scent preference which may be connected to previous exposure to such scents. For the dimension of perceived temperature, employment status has a significant effect on visual and olfactory acuity which may also be connected to pollution exposure while gender affects olfactory acuity. Future research may explore the effects of previous experience with the stimuli, personality, physiological disposition, culture and genetics as this present study has proven that these can also underlie perception of visual and olfactory stimuli.